Enhanced Magnetic Properties of Co-Doped BiFeO3 Thin Films via Structural Progression - Liang Bai; Mingjie Sun; Wenjing Ma; Jinghai Yang; Junkai Zhang; Yanqing Liu (Nanomaterials, 2020)
Co3+ doping in BiFeO3 is expected to be an effective method for improving its magnetic properties. In this work, pristine BiFeO3 (BFO) and doped BiFe1-xCoxO3 (BFCxO, x = 0.01, 0.03, 0.05, 0.07 and 0.10) composite thin films were successfully synthesized by a sol–gel technique. XRD and Raman spectra indicate that the Co3+ ions are substituted for the Fe3+ ion sites in the BFO rhombohedral lattice. Raman vibration of oxygen octahedron is obviously weakened due to the lattice distortion induced by the size mismatch between two B-site cations (Fe3+ and Co3+ ions), which has an impact on the magnetic properties of BFCxO. SEM images reveal a denser agglomeration in Co-doped samples. TEM results indicate that the average size of grains is reduced due to the Co3+ substitution. XPS measurements illustrate that the replacement of Fe3+ with Co3+ effectively suppresses the generation of oxygen defects and increases the concentration of Fe3+ ions at the B-site of perovskite lattice. Vibrating sample magnetometer (VSM) measurements show that the remanent magnetization (Mr) of BFC0.07O (3.6 emu/cm3) and the saturation magnetization (Ms) of BFC0.10O (48.84 emu/cm3) thin film both increase by approximately two times at room temperature, compared with that of the pure BFO counterpart.